Estimation Effect of Weather Factors on Biogas Emissions Rate (Methane) from Landfill Stations in Baghdad, Iraq - Ali Razaq; Ahmed Hassoon (Iraqi Geological Journal, 2022)
The topic of this study examines the release of methane gas from the landfill stations in the Baghdad Governorate, the biological decomposition and anaerobic decomposition (absence oxygen) breakdown of garbage, after the garbage is buried in the landfill stations. The objective of this research is to estimate the methane (CH4) emission rate, from landfill stations ineffective weather factors such as (temperature, wind speed and direction), and also the possibility of using it as a source of sustainable energy in Baghdad Governorate. Garbage was collected in nine congregational stations, located on both sides of Karkh and Rusafa. Through study the period from 2016 to 2018, the highest methane emission rate was 0.046 GgYr-1 in 2018, and the lowest methane emission rate was 0.0077GgYr-1 in 2017, while the annual total municipal solid waste (MSW) was 2421808m3 and 407665m3 respectively. The results also showed a monthly greatest amount of methane emission rate occurred in July and August at a rate 0.003 Gg/ month with average temperatures of 36Co and average wind speed of 4.3 m/s, while the lowest occurred in January and February at a rate 0.001Gg/month, with an average temperature of 11Co and average wind speed of 3 m/s, the prevailing wind direction is about 270o-337.5o. By converting municipal solid waste disposal sites (open dumps) to sanitary landfills with methane collection and utilization facilities. The methane from the garbage disposal sites can be used as a sustainable energy source to generate electrical energy estimated years 2016, 2017 and 2018, from the methane emission rate of about 57.666 kW/h -105.661kW/h.